DNA identification of skeletal remains by investigator's intuition. Issue 1 (December 2019) - Ricci, U.; Centrone, C.; Gerundino, F.; Pelo, E.
Abstract: In June 2006 a decapitated woman was found in a parking area of the motorway in the area of Prato (Florence). Since the body was beheaded and no victim's documents or objects were present at the crime scene, identification at that time was impossible. However, DNA profile from woman's bones were collected. In the same year (2003), a mother had reported her daughter's disappearance but the two events were not related at that time. About ten years later the mother's DNA profile was finally acquired for a genetic identification of another girl's body found in the Ferrara area. These genetic profiles were completely discordant. All these genetic comparisons were carried out on behalf of the prosecutors of the cities involved in the findings of the bodies and in the disappearance complaints, but due to the lack of a database the events remained disconnected. In January 2017, the head of the scientific police of Prato who had followed the investigation and questioned the mother of the missing girl found about ten years later, suggested to the magistrate to order the comparison of the mother's DNA with the genetic profile of the bones found in 2006. This comparison finally allowed the identification of the missing daughter. This story highlights the importance of having forensic DNA database to search for missing persons and how the investigator's intuition can play a key role in resolving criminal cases. In fact, databases of unknown bodies and relatives of missing persons were created in Italy as a part of national DNA database just at the beginning of 2018.